(untitled) (Heritage, 2024)
Human history has been marked by various terrorist activities, making it possible to assert that terrorism characterizes almost all epochs of human civilization. From the Jewish zealot group known as the Sicarii, through the Shiite religious sect of the Assassins in the 11th century, to the French Revolution, the Spring of Nations, and well-known bomb attacks and assassinations, terrorism as a form of violence represents one of the leading security threats. Waves of terrorism in the last 100 years have swept through modern civilization, and each wave brings with it a new form of terrorist activity. One such wave "hit" the territory of the former Yugoslavia, bringing to light a terrorist entity known in the literature as the Ustasha - Croatian Revolutionary Movement. This movement, its emergence, and evolution will be the subject of a detailed analysis in this scientific work. Special attention will also be devoted to the radical ideology of the movement, terrorist activities, and crimes, especially those against the Serbian population.